Analytical modelling of perforated geometrical domains by the R-functions - Semerich, Yuriy (Mathematical Modelling and Analysis, 2020)
This paper deals with the construction of boundary equations for geometric domains with perforation. Different types of perforated geometric domains are considered. The R-functions method for analytical modelling of perforated geometrical domains is used. For all constructed equations, function plots are obtained.